Fuzzy Logic Control of a Head-movement Based Semi-autonomous Human–machine Interface - Özlük, Yasir; Akman Aydin, Eda (Journal of bionics engineering, 2023)
Quadriplegia is a neuromuscular disease that may cause varying degrees of functional loss in trunk and limbs. In such cases, head movements can be used as an alternative communication channel. In this study, a human–machine interface which is controlled by human head movements is designed and implemented. The proposed system enables users to steer the desired movement direction and to control the speed of an output device by using head movements. Head movements of the users are detected using a 6 DOF IMUs measuring three-axis accelerometer and three-axis gyroscope. The head movement axes and the Euler angles have been associated with movement direction and speed, respectively. To ensure driving safety, the speed of the system is determined by considering the speed requested by the user and the obstacle distance on the route. In this context, fuzzy logic algorithm is employed for closed-loop speed control according to distance sensors and reference speed data. A car model was used as the output device on the machine interface. However, the wireless communication between human and machine interfaces provides to adapt this system to any remote device or systems. The implemented system was tested by five subjects. Performance of the system was evaluated in terms of task completion times and feedback from the subjects about their experience with the system. Results indicate that the proposed system is easy to use; and the control capability and usage speed increase with user experience. The control speed is improved with the increase in user experience.